The joint estimation of Filipino child’s participation in schooling and employment and new stylized facts on the Philippine child labor situation - Rufino, Cesar C. (Animo Repository, 2015)
This study utilized the recently available public use raw data file of the 2011 round of the Annual Poverty Indicator Survey (APIS) to establish the latest stylized facts on the Philippine child labor situation. Public use file of the 2008 APIS was also used to generate comparative descriptives. It is also an attempt to jointly estimate the schooling and employment choices of Filipino children via the multinomial logit model that used the four different permutations of schooling and employment as the mutually exclusive and exhaustive categories of choice. A value added feature of the study is the use of survey design consistent procedures in establishing the descriptives as well as the estimates of the main empirical model. Tabulated summaries of the results reveal some alarming developments in the child labor situation of the country. The outcome of the econometric modeling confirms the empirical relevance of certain covariates discussed in the literature concerning schooling/work choice formation of Filipino children. © 2015 by De La Salle University.